Immunoprecipitation of ROR1 - Vincent Bicocca; Jeffrey Tyner (Bio-Protocol, 2013)
ROR1 is a receptor tyrosine kinase family member studied for its roles in development and cancer. Here we describe a protocol for immunoprecipitation of endogenous ROR1 from t(1;19) (a disease subtype categorized by its chromosome translocation) acute lymphoblastic leukemia immortalized cell lines.